Effect of oral treatment of synthetic androgens on sex ratio, survival and growth rates, in three strains of tilapia - Jiménez-Badillo, Ma. de Lourdes; Arredondo-Figueroa, José Luis (HIDROBIOLÓGICA, 2017)
The effect of dietary administration of the synthetic androgens 17 ?-methyltestosterone MT (40 mg), luoxymesterone FM (1 mg) and propionate testosterone PT (50 mg) per kg of feed, on Stirling strain (Oreochromis niloticus, Linnaeus, 1757), Red strain (Oreochromis niloticus, Linnaeus, 1757) and the hybrid Rocky Mountain (Oreochromis niloticus, Linnaeus, 1757 x Oreochromis aureus, Steindachner, 1864) fry, was evaluated during a 30 day trial to induce sex reversal. The most efficient androgen was MT for male ratio (92%), mean percentage survival and specific growth rate. TP was th least efficient (67 % male). The percentage of males from FM treatment was 80.6%, but this can be improved when time period or hormone-treated dosage are increased. Thus, the FM androgen could be recommended for a successful sex reversal, instead of MT. The Stirling strain (O. niloticus) had the best results when compared to the other two strains of tilapia.